Rehabilitation in post-COVID patients. A single center experience. (14th October 2021) - Villani, G Q; Villani, M; Halasz, G; Rosi, A; Piepoli, M F
Abstract:  : The COVID 19 disease is frequently associated with significant disability related to intensive care unit-acquired weakness, decontitioning, myopathies and neuropathies. However there are no data on the results of a specific rehabilitative treatment in this group of patients. The aim of our work was to evaluate the effectiveness f a personalized rehabilitative therapy in group of post-COVID patients (A, 47 patients, average age 65.3±11.6 y, 27 M, ) comparing the results with a group of post-cardiosurgical patients COVID 19 negative (B, 47 patients, average age 63.5±10.3 y, 29 M) evaluating the degree of clinical complexity (Rehabilitation Complexity Scale, RCS-E V13) and the degree of autonomy recovery (Six-minute walking test SMWT, Barthel Index, BI) pre and post-treatment. In Group A patients the Rehabilitation program is associated with a significant improvement in autonomy recovery (BI admission 29.7±20 vs discharge 72.7±28.6 p<0.005, SMWT admission 146±25 vs 318±18 m, p<0.005) and in clinical complexity (RCS admission 10.9±1.1 vs discharge 5.3, p<0.05). At admission the comparison between Group A vs B has show: 1. a reduced pre-rehabilitation hospital stay (days) in Group Vs A (B 8.2±2 vs 31±5 0.005) 2. a similar degrre of clinical complexity (RCS scale A 10.9±1.1 vs 1.6±11.2 p ns) 3. a greater loss autonomy in post-COVID patients (BI scale A 29.7±20 vs B 47.7±19, p 0.05; SMWT A 145±25 m vs B 255±18 m, p 0.05) After a similar period of rehabilitation (A 29.7±12.8 days vs B 29.6±10 days, p ns) we observed in both Groups: 1. a reduction of clinical complexity ((RCS scale A 5.3±2 vs 6.6±2 p ns 2. an improvement of degree of autonomy recovery ((BI scale A 72.7±28 vs B 47.7±19, p ns; SMWT A 385±18 m vs B 410±25m, p ns) Conclusions: Post-COVID patients show a greater loss of autonomy than post-cardiosurgery patients. Rehabilitative treatment has proven effective in ensuring adequate functional recovery with similar results to those obtained in the population of cardiological subjects COVID 19 negative. Funding Acknowledgement: Type of funding sources: None.